RESOURCE MANAGEMENT OF FAMILY FARMS - Rajić, Zoran; Jelić, Sreten; Živković, Dragić; Ralević, Nebojša (Economics of Agriculture, 2007)
Family farms are faced with an ever-rising competitiveness on the market. In order to meet the requirements on the market family farms are obliged to use current resources, raise labor productivity and adapt the production program to the needs of the consumers. Small farms are unlikely to succeed on the market considering the lack of both human and material resources. Their only chance is production intensification, competitive crop production and establishment of associations. The aim of the study was to develop models for different family farm types taking into account the constraints in order to enable an income which would meet the needs of household members. A comparison of the models would enable the determination of competitiveness of some production lines and of the farms involved. This is of principal interest to regions where there are numerous producers disposing of small agricultural land areas and focused on the production of one or two products (raspberry or any other berry fruit, plums and tobacco).